A New Repeated Mining Method With Preexisting Damage Zones Filled for Ultra-Thick Coal Seam Extraction – Case Study - Chen, Liang; Zhang, Dongsheng; Fan, Gangwei; Zhang, Shizhong; Wang, Xufeng; Zhang, Wei (Frontiers in Earth Science, 2022)
Arbitrary mining activities done by previous small-scale mines left many irregular damage zones in ultra-thick coal seam, consequently leading to serious roof caving disasters and recovery ratio decline during repeated mining. Pre-filling the damage zones is an effective method to prevent mining-induced geological disasters. In this paper, a novel method regarding damage zone filling-based repeated mining (FBRM) was proposed by combining the lower cutting layer (LCL) with the upper key bearing layer (UKBL) based on analysing the disaster state when the workface passes through damage zones. To determine filling thickness, a method for calculating UKBL thickness was developed to preliminarily identify the filling thickness parameters of UKBL. On this basis, a numerical model incorporating damage zones and coal extractions was established to investigate the impact of UKBL thickness on fracture propagation and the maximum principal stress profiles around the damage zones. The proposed FBRM method was verified using the ground pressure data collected from Panel B909 of Pingshuo No.2 Colliery. The results show that, (1) the filling material with low strength and good cuttability is suitable for LCL, while material with high strength and robust bearing capacity is for UKBL; (2) with increasing the UKBL filling thickness, the height of fracturing decreases obeying a negative exponential function, suggesting a good effectiveness of damage zone pre-filling technique; (3) as the UKBL filling thickness rises to 5 m, the maximum principal stress relocates from the area above both damage zones to the area closely in front of the workface, indicating a filling thickness threshold of 5 m that can ensure roof stability; (4) the maximum working resistance and bed separation were 11800 kN and 26 mm respectively when the workface passed through damage zones B and E, favoring a good reliability of the FBRM method. The research can provide best-practice references for preventing roof caving disasters while exploiting the ultra-thick coal deposits affected by previous mining activities.